TEORI KOMPENSASI MARAH DALAM PERSPEKTIF PSIKOLOGI ISLAM - Indah Wigati (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Normally, there are three basic emotions of human beings since the human born, such as emotionally upset, excited and scared. Angry compensation theory is a theory that the human ability to divert the anger feelings that arise and it is human nature given by God. The compensation can be received directly or indirectly, Prinsiply, in direct competition if the person able to control their feeling of temper it’s can protect them from all diseases such as; heart disease, hypertension and others. In other hand, indirect compensation which is person will get the reward from the God that heaven will be included, and will be increased in rank highest, including pious, looks wise and admired by many people. Angry in man is something that is natural from God that cannot be removed by anyone but can be managed positively angry. Angry that someone means the positive impact will be more assertive and respected, can improve a person's self confidence and can overcome fear if someone can manage angry emotions well.